Energeticky úsporný rodinný dům - Jastřembská, Monika (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Projekt se zabývá novostavbou rodinného domu v Pukanci. Cílem této práce je vytvořit projektovou dokumentaci pro provedení stavby. Dům je navrhován jako dvougenerační. Objekt má dvě patra a je nepodsklepený. Je zděný z keramických tvárnic Porotherm a má pultovou střechu. Budova je situována na rovinatém pozemku.

The project delas with building a new detached house in Pukanec. The aim of the work is to create documents for building construction. Te house is designed for two generations. The building has two floors and no basement. It is based on brick system Porotherm and it has a shed roof. The building is situated in flat terrain.
Energy-saving detached house
Keywords: Rodinný dům Pultová střecha Dřevěná pavlač Tvárnice Porotherm; Detached house Shed roof Wooden gallery Porotherm blocks